The impacts of selling expense structure on enterprise growth in large enterprises: A study from Vietnam - Nguyen Van Cong; Thi Ngoc Lan Nguyen; Thanh-Hang Pham; Song Hoa Vu (Journal of Risk and Financial Management, 2020)
This study intends to examine the impact of selling expense structure on the business growth of 255 Vietnamese large-scale enterprises in three different industries (Consumer Staples, Industrials, and Manufacture) listed on the Vietnamese Stock Exchange over four years from 2015 to 2018. By using STATA software (StataCorp LLC, 4905 Lakeway Drive, College Station, Texas 77845-4512, USA), the research outcomes indicate that both labour expense and depreciation expense have a negative influence on revenue growth and firm size growth but positive influence on profit growth while materials and tools expenses negatively affect all three dependent variables. Furthermore, an increase in the proportion of outsourcing expenses and other selling expenses would result in a significant increase in revenue but a decline in the profit of these companies. From this research results, large-scale enterprises should consider changing the selling expense structure as they spend too much on outsourcing and other selling expenses (60%-70% total selling expense) but too little on labour, which plays an important role in upgrading the profitability of these enterprises.
Keywords: 330; big enterprises; enterprise growth; selling expense structure